청소년의 자아정체감, 사회적지지와 정신건강과의 관계 - 구승신(Seung-Shin Koo); 정옥희(Ok-Hee Jung); 장성화(Sung-Hwa Jang) (한국콘텐츠학회 논문지, 11(9), 2011)
The purpose of this study was to analyze the Relationshipss of Ego-Identity, Social support and Mental health of Adolescents. The subjects for this study were 347 adolescents composed of 169 middle school students, 347 high school students in Kyung-gi Do. The data was conducted by using a correlations coefficient and the multiple regression analysis. The results of the study were as follows: First correlations among measured subordinate variables of Ego-Identity, Social support on subordinate variables of Mental health of Adolescents were significant. except compulsiveness and support of friend, hostility, phobia and support of teacher, somatization and confidence of one's future, intimacy, support of teacher, support of friend, depression, psychosis and confidence of one's future. Second, the result of the multiple regression analysis, the significant variables affected mental health are ranked in the order of self-acceptance, aim for goal, support of parents, intimacy, independence. while confidence of one's future, leading, support of teacher, support of friend are not significant. The result of this study shows that adolescents of high level of self-acceptance, aim for goal, intimacy, independence and perceived highly support of teacher are high level of mental health. 본 연구에서는 청소년의 자아정체감, 사회적지지와 정신건강과의 관계를 검증하였다. 연구대상은 경기도 지역 K시에 소재한 중 고등학교 각 2개 학교의 중학생 169명, 고등학생 178명으로 총 347명을 대상으로 상관계수와 중다회귀분석을 실시하였다. 그 결과는 다음과 같다. 첫째, 청소년의 자아정체감, 사회적지지, 정신건강 간의 관계를 살펴보면, 청소년의 자아정체감, 사회적지지의 하위변인에서 정신건강의 하위변인 중 강박증과 친구지지, 적대감 및 공포증과 교사지지, 신체화와 미래확신성, 친밀성, 교사지지, 친구지지, 우울증과 미래확신성, 정신증과 미래확신성을 제외한 모든 하위영역에서 상관이 있는 것으로 나타났다. 둘째, 중다회귀분석 결과, 정신건강에 영향을 미치는 가장 높은 변인은 자기수용성, 목표지향성, 부모지지, 친밀성, 주체성 순으로 나타난 반면, 미래확신성, 주도성, 교사지지, 친구지지는 통계적으로 유의미한 예측변인이 아닌 것으로 나타났다. 본 연구의 결과는 자기수용성, 목표지향성, 친밀성, 주체성 수준이 높은 청소년과 부모지지를 높게 지각하는 청소년의 정신건강 수준이 높음을 나타내고 있다.